Business valaution - Pegas Nonwovnes SA - Mihardja, André; Maříková, Pavla, 1965-; Legát, Viktor; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2008)
This thesis concerns valuation of Pegas Nonwovens SA. The valuation was carried out using DFC entity method and market comparable approach. The valuation also contains financial analysis of the company, market analysis and projected financial statements and value drivers.
Vedoucí práce: Pavla Maříková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2008
Rok obhajoby 2008
Keywords: podnikání a právo [obor dipl. práce]; diplomové práce; master's theses